Ultrasonographic accuracy in evaluating response of clipped lymph nodes in targeted axillary dissection in breast cancer - Ozge Aslan; Aysenur Oktay; Berk Goktepe; Gurdeniz Serin (Scientific Reports)
Abstract This study aimed to evaluate the diagnostic accuracy of ultrasonography in assessing the response of clipped axillary lymph nodes to neoadjuvant chemotherapy. Between February 2022 and September 2023, 43 patients who underwent axillary lymph node marking for targeted axillary dissection were retrospectively analyzed. Ultrasonography parameters such as the number, size, shape, cortical thickness, hilum status, and treatment response of the clipped lymph node were assessed. Post-surgery pathology results served as the gold standard. Ultrasonography revealed 70% complete and 30% partial response, while pathology results showed 51% complete response, 9% micro-metastases, and 40% macro-metastases. The diagnostic accuracy of ultrasonography was 81.4%, with 61.9% sensitivity and 100% specificity. A significant correlation was found between clipped node response in ultrasound and pathology. Additionally, a notable association was observed between clipped node response on ultrasonography, molecular subtype of the breast mass, and the mass’s response to NAC. Assessing the treatment response of clipped lymph nodes with preoperative ultrasound, followed by surgical excision using needle wire localization, can be a viable alternative to axillary dissection, offering low false-negative rates.